2017
DOI: 10.1097/j.pain.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic tone does not influence pain levels during placebo interventions in patients with chronic neuropathic pain

Abstract: Placebo effects have been reported in patients with chronic neuropathic pain. Expected pain levels and positive emotions are involved in the observed pain relief, but the underlying neurobiology is largely unknown. Patients with neuropathic pain are highly motivated for pain relief, and as motivational factors such as expectations of reward, as well as pain processing in itself, are related to the dopaminergic system, it can be speculated that dopamine release contributes to placebo effects in neuropathic pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 77 publications
(161 reference statements)
0
20
0
2
Order By: Relevance
“…In a recent study, we demonstrated large (Cohen's d = 1.54) and significant (p = 0.002) placebo effects on ongoing neuropathic pain intensity that were highly associated with expectations for pain relief (Skyt et al, 2017). In the present study, we tested the association between the CPM response and the magnitude of the observed placebo effect.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In a recent study, we demonstrated large (Cohen's d = 1.54) and significant (p = 0.002) placebo effects on ongoing neuropathic pain intensity that were highly associated with expectations for pain relief (Skyt et al, 2017). In the present study, we tested the association between the CPM response and the magnitude of the observed placebo effect.…”
Section: Introductionmentioning
confidence: 83%
“…Although CPM and placebo effects have both been shown to involve the endogenous opioid system (Levine et al, 1978;Willer et al, 1990) and be influenced by expectations (Vase et al, 2005;Lariviere et al, 2007;Bjorkedal and Flaten, 2012;Nir et al, 2012;Cormier et al, 2013;Petersen et al, 2014;France et al, 2016), the impact of these mechanisms is likely to vary. Specifically, expectations seem essential for eliciting placebo effects in neuropathic pain (Petersen et al, 2014;Skyt et al, 2017) but only modestly related to CPM responses (Nir et al, 2012). In addition, several studies suggest that endogenous opioids mediate expectancy-induced placebo effects (Levine et al, 1978;Eippert et al, 2009).…”
Section: Cpm and Placebo Effects In Neuropathic Pain Do Not Seem To Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Haloperidol, a dopamine D 2 /D 3 receptor antagonist, had no effects on placebo analgesia at behavioral or neural level, as measured using functional magnetic resonance imaging (Wrobel et al, 2014). In a recent pharmacological study, haloperidol or levodopa failed to influence placebo effect in patients with neuropathic pain, although the level of expectancy was changed (Skyt et al, 2018). Importantly, these studies did not measure striatal dopamine neurotransmission directly, and it is also not known whether higher drug doses would have revealed significant placebo effects.…”
Section: Dopamine In Placebo Analgesiamentioning
confidence: 99%
“…These regions may influence brain states in a similar manner as exogenous manipulation, such as anesthetics, may do (Hamilton et al, 2017; Hudetz et al, 2015). Individual differences in subconscious behavior may be mediated by tone/connectivity of reward-aversion systems as they relate to dopaminergic tone and release (Marcott et al, 2014; Skyt et al, 2017) and to individual differences in inhibitory neurotransmitters (Boy et al, 2010). With respect to the latter, it is notable that GABA levels predict responsivity to analgesic efficacy in patients with fibromyalgia (Harris et al, 2013), suggesting an underlying state of pain evolution in these patients.…”
Section: The Tipping Point: Neurobiological Processes Brain Dysfumentioning
confidence: 99%